1992
DOI: 10.1136/adc.67.5.640
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of normal micturition in myelomeningocele patients.

Abstract: Among 108 consecutive patients with myelomeningocele aged 5-12 years initiaily treated by a selective policy, seven (6-5%) achieved spontaneous urinary continence, five with normal micturition and two with urgency. AlU had positive conus reflexes and incomplete cord lesions which, with one exception, comprised motor as weli as sensory sacral sparing.Neuropathic bladder, with urinary incontinence and the risk of renal complications, is a major problem for patients with myelomeningocele and especially for those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…Accordingly, only 1 out of 21 patients suff ered a decrease of renal function postoperatively in the reported series. The rate of spontaneous urinary continence in children with meningomyelocele is described to be as low as 6 -22 % [16,17] . Social urinary continence can be accomplished by CIC and anticholinergics in 75 -80 % of patients with neurogenic bladder dysfunction [18] .…”
Section: Results ▼mentioning
confidence: 98%
“…Accordingly, only 1 out of 21 patients suff ered a decrease of renal function postoperatively in the reported series. The rate of spontaneous urinary continence in children with meningomyelocele is described to be as low as 6 -22 % [16,17] . Social urinary continence can be accomplished by CIC and anticholinergics in 75 -80 % of patients with neurogenic bladder dysfunction [18] .…”
Section: Results ▼mentioning
confidence: 98%
“…Reimer et al found that only 6% of the patients with myelomenigocele achieved spontaneous urinary continence [11]. However, Ottolini et al reported that 72% of the children using CISC and pharmacotherapy were dry during the day [12], but in a series from Houston, 47/76 patients with improvement of bladder compliance by pharmacotherapy and CISC remained wet between catheterizations [5].…”
Section: Discussionmentioning
confidence: 96%
“…Some 30% of patients with myelomeningocele have positive conus reflexes, regardless of the level of the lesion [ 2], although results indicate that in only a small proportion of cases is this associated with sacral sensory sparing, and in a smaller fraction still with motor sparing [ 1]. Occasional examples of incomplete cord lesions are encountered in patients with negative conus reflexes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that whilst the great majority of patients with myelomeningocele have a neuropathic bladder, a small proportion (6% by the most recent estimate [ 1]) are free of this complaint, all having an incomplete cord lesion and almost all with motor as well as sensory sparing. So far undescribed is a subcategory of patients with a neuropathic bladder and an incomplete cord lesion who as a result can gain some measure of urinary continence spontaneously, but who are still at risk of secondary upper urinary tract complications; such patients form the basis of this report.…”
Section: Introductionmentioning
confidence: 99%